Characterization of Women in Kazakh Music Culture - Autolkyn Toktagon (International Journal of Science and Society, 2019)
This article discusses the role of women in traditional musical culture in Kazakhstan and addresses the life and creativity of Dina Nurpeisova (1861-1955). Dina was a respected stupid player, student of the famous kyushi [ii] Qurmanghazy and of a super kyuishi. The article examines Dina's life based on archives that became available only after Kazakhstan became independent. From the 1940s to the 1990s, the Soviet media ended the oppressive conditions of the Kazakh women's revolution. He claimed that women in the "wild" Kazakhstan, who had no control or their own culture, achieved happiness until after the creation of the Soviet Union. The printed media focused specifically on the character of the famous kyuishi Dina Nurpeisova (1861-1955), who described her as a Kazakh woman released under Soviet rule. Since then, Dina has ignored this view, but this misunderstanding of the feminine position in the revolutionary Kazakh culture has become the norm. The result is that Dina is considered a unique phenomenon in Kazakh music culture. Although she undoubtedly had unusual gifts (people even called her "Kyu's mother", which amounts to calling Kyur's father "Qurmanghazy"), Dina was not the only officially recognized woman in Kazakh traditional culture. The Kyuishi women ruled the states and the women occupied a very high position in the traditional society, as evidenced by many excellent names of singers, poetesses, actresses, kyuishis and warriors that they have preserved until today. At the same time, Dina Nurpeisova is a special place among these prominent women in Kazakh. The purpose of this study is to free Dina's biography from antiquated and wrong interpretations and to present his artistic approach based on in-depth knowledge.